Cell diagnostics : images, biophysical and biochemical processes in allelopathy - Roshchina, V. V. (Viktorii͡a Vladimirovna); Narwal, Shamsher S. (Science Publishers, 2007)
Topics discussed in this title include cellular model systems, new methods of microscopy in cellular diagnostics and methods of analytical biochemistry and biophysics.